Problematic Alcohol Use among University Students - Mekonen, Tesfa; Fekadu, Wubalem; Chane, Tefera; Bitew, Shimelash (Frontiers in Psychiatry, 2017)
Background: Alcohol is attributable to many diseases and injury related health conditions, and it is the fifth leading risk factor of premature death globally. Hence, the objective of this study was to assess the proportion and associated factors of problematic alcohol use among University students. Material and methods: Cross sectional study was conducted among 725 randomly selected University students from November to December 2015. Data were collected by self-administered questionnaire and problematic alcohol use was assessed by Alcohol Use Disorder Identification Test (AUDIT). Chi square test was used to show association of problematic use and each variable and major predicators was identified using logistic regression with 95% confidence interval; and variables with p value less than 0.05 were considered statistically significant. Results: About 83 (11.4%) of the samples were problematic alcohol users of which 6.8% had medium level problems and 4.6% had high level problems. Significantly associated variables with problematic alcohol use among students were; presence of social phobia [AOR = 1.7, 95% CI: 1.0, 2.8], lifetime use of any substance [AOR = 6.9, 95%CI: 3.8, 12.7], higher score in students cumulative grade point average (CGPA) [AOR = 0.6, 95% CI: 0.4, 0.9], and having intimate friend who use alcohol [AOR = 2.2, 95% CI: 1.3, 3.8]. Conclusion: Problematic alcohol use among university students was common and associated with social phobia, poor academic achievement, lifetime use of any substance, and peer pressure. Strong legislative control of alcohol in universities is important to reduce the burden of alcohol.